Distribuição espacial de Dilobopterus costalimai Young (Hemiptera: Cicadellidae) em citros na região de Taquaritinga, SP - Maruyama, Wilson I. [UNESP]; Barbosa, José C. [UNESP]; Fernandes, Marcos G. [UNESP]; Yamamoto, Pedro T. (My University, 2002)
Dilobopterus costalimai Young is one of the most important pests in Brazilian citrus crop because it transmits Xylella fastidiosa, a bacterium that causes Citrus Variegated Chlorosis (CVC). We studied the spatial distribution of the insect, in order to develop a sampling plan to determine the proper moment to control the pest. D. costalimai was collected fortnightly, between 11/1999 until 4/ 2000, in a thirteen-year-old citrus orchard, where no insecticide was sprayed against this insect. Thirteen samples were performed in a grid of 100 yellow sticky traps (10 × 25 cm) in Taquaritinga County, Sao Paulo State. The variance of the sampling was higher than the mean in all samplings, with index ratio variance/mean (I) between 1.07 and 2.90, Morisita index between 1.07 and 1.57, k exponent of negative binomial distribution between 1.56 and 14.79. The chi-square goodness-of-fit test to Poisson distribution were not significant in seven samplings, however adjust to negative binomial were not significant in all samplings. The index b of Taylor's Power Law was 1.3054, thus showing an aggregated distribution for this species in the field.
Spatial distribution of Dilobopterus costalimai Young (Hemiptera: Cicadellidae) in citrus area of Taquaritinga, São Paulo State, Brazil
Keywords: Binomial negative distribution; Citrus sinensis; Insecta; Poisson distribution; Sampling; Sharpshooter